A three‐dimensional PbII coordination framework: poly[[μ4‐(E)‐2, 2′‐(diazene‐1, 2‐diyl)dibenzoato]dimethanollead(II)]. Issue 7 (5th June 2014) - Liu, Lei‐Lei; Yu, Cai‐Xia; Hua, Lei; Lin, Lu
<x xml:space="preserve">Abstract</x> In the title coordination polymer, [Pb(C14H8N2O4)(CH3OH)2]n, the asymmetric unit contains half of a PbII cation, half of a 2, 2′‐(diazene‐1, 2‐diyl)dibenzoate dianionic ligand (denoted L2−) and one methanol ligand. Each PbII centre is eight‐coordinated by six O atoms of chelating/bridging carboxylate groups from four L2− ligands and two O atoms from two terminal methanol ligands, forming a distorted dodecahedron. The [PbL2(MeOH)2] subunits are interlinked via the sharing of two carboxylate O atoms to form a one‐dimensional [PbL2(MeOH)2]n chain. Adjacent chains are further connected by L2− ligands, giving rise to a two‐dimensional layer, and these layers are bridged by L2− linkers to afford a three‐dimensional framework with a 41263 topology.